Activation of TLR3/interferon signaling pathway by bluetongue virus results in HIV inhibition in macrophages. Issue 12 (21st August 2015) - Dai, Ming; Wang, Xu; Li, Jie‐Liang; Zhou, Yu; Sang, Ming; Liu, Jin‐Biao; Wu, Jian‐Guo; Ho, Wen‐Zhe
ABSTRACT: Bluetongue virus (BTV), a nonenveloped double‐stranded RNA virus, is a potent inducer of type I interferons in multiple cell systems. In this study, we report that BTV16 treatment of primary human macrophages induced both type I and III IFN expression, resulting in the production of multiple antiviral factors, including myxovirus resistance protein A, 2', 5'‐oligoadenylate synthetase, and the IFN‐stimulated gene 56. Additionally, BTV‐treated macrophages expressed increased HIV restriction factors (apolipoprotein B mRNA‐editing enzyme catalytic polypeptide 3 G/F/H) and CC chemokines (macrophage inflammatory protein 1‐α, macrophage inflammatory protein 1‐β, regulated on activation of normal T cell expressed and secreted), the ligands for HIV entry coreceptor CC chemokine receptor type 5. BTV16 also induced the expression of tetherin, which restricts HIV release from infected cells. Furthermore, TLR3 signaling of macrophages by BTV16 resulted in the induction of several anti‐HIV microRNAs (miRNA‐28, ‐29a, ‐125b, ‐150, ‐223, and ‐382). More importantly, the induction of antiviral responses by BTV resulted in significant suppression of HIV in macrophages. These findings demonstrate the potential of BTV‐mediated TLR3 activation in macrophage innate immunity against HIV.—Dai, M., Wang, X., Li, J.‐L., Zhou, Y., Sang, M., Liu, J.‐B., Wu, J.‐G., Ho, W.‐Z. Activation of TLR3/interferon signaling pathway by bluetongue virus results in HIV inhibition in macrophages. FASEB J. 29, 4978–4988 (2015). www.fasebj.org